Body mass index and risk of sick leave: A systematic review and meta‐analysis. Issue 6 (1st August 2019) - Amiri, Sohrab; Behnezhad, Sepideh
Summary: Body mass index (BMI) is related to different health dimensions and can be a risk factor for diseases. Our objective was to systematically review and meta‐analysis the association BMI and the risk of sick leave. Four databases were searched for articles until late December 2018 and the results of the studies were extracted and combined using random effects methods. Several sub‐group analyses were conducted as well as bias of publication were measured. A total of 23 longitudinal studies entered into meta‐analysis. BMI ≥ 25 was a risk factor for sick leave; the risk ratio (RR) is equal to 1.20 with confidence interval (CI): 1.14 to 1.28. In the overweight, this result was achieved: RR = 1.09 and CI = 1.04 to 1.15 ( P = 0.001) and in the obesity, RR = 1.30 and CI = 1.19 to 1.42 ( P  < 0.001). In both men and women, overweight and obesity were both a risk factor for sick leave. A high BMI is a risk factor that threatens health in different dimensions and therefore, overweight/obesity prevention and treatment should be given increasing attention. This will reduce the burden of illness and its consequences.